Pi Day Challenge 2017 - Mitosis

Geometry Level 4

The diagram above shows a big red circle with diameter 314159 , tangent to a cyan circle with diameter 26535 and a green circle with diameter 23846 , which are tangent to each other and also to a purple circle with diameter 89793 .

The length of the pink line segment between the two points of tangency can be expressed in its simplest form as 2 105458935 50381 ( a b + c ) , \dfrac{2\sqrt{105458935}}{50381}\big(a\sqrt{b}+\sqrt{c}\big), where a , b a,b and c c are positive integers with b , c b,c square-free. Find a + b + c a+b+c .


Happy Pi Day 2017.

Index of Pi Day Challenges


The answer is 19011070622.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

K T
Nov 22, 2020

I use c , g , p , r c,g,p,r for the diameters of the cyan, green, purple and red circles, and C , G , P , R C,G,P,R for their centres.

Translate the pink line, so that one of its endpoints is in P P . call its other endpoint Q Q We now have a rectangular triangle P Q R PQR with sides Q R = ( r p ) / 2 , P Q = L QR=(r-p)/2, PQ=L (the requested length) and hypothenuse P R PR .

First we will find P R PR

Drop a line from R R onto C G CG , meeting it at M M , its length is a a We now have formed two right angled triangles:

  • R G M RGM with sides R G = r g 2 , G M = d , R M = a RG=\frac{r-g}{2}, GM=d, RM=a
  • R C M RCM with sides R C = r c 2 , C M = e , R M = a RC=\frac{r-c}{2}, CM=e, RM=a
  • we also have G M + M C = G C GM+MC=GC , so d + e = g + c 2 d+e=\frac{g+c}{2}

We get equations ( r g 2 ) 2 = a 2 + d 2 (\frac{r-g}{2})^2=a^2+d^2 and ( r c 2 ) 2 = a 2 + e 2 (\frac{r-c}{2})^2=a^2+e^2 .

d 2 e 2 = ( r g 2 ) 2 ( r c 2 ) 2 = 2 r ( c g ) + g 2 c 2 4 d e = g 2 c 2 + 2 r ( c g ) 2 ( c + g ) d^2-e^2=(\frac{r-g}{2})^2-(\frac{r-c}{2})^2 =\frac{2r(c-g)+g^2-c^2}{4}\Rightarrow d-e=\frac{g^2-c^2+2r(c-g)}{2(c+g)} and since e + d = c + g 2 e+d=\frac{c+g}{2} we know e e and d d :

d = ( d + e ) + ( d e ) 2 = g 2 + c g + r ( c g ) 2 ( c + g ) d=\frac{(d+e)+(d-e)}{2}=\frac{g^2+cg+r(c-g)}{2(c+g)} e = ( d + e ) ( d e ) 2 = c 2 + c g r ( c g ) 2 ( c + g ) e=\frac{(d+e)-(d-e)}{2}=\frac{c^2+cg-r(c-g)}{2(c+g)} a = r c g ( r c g ) c + g a=\frac{\sqrt{rcg(r-c-g)}}{c+g}

Drop a line from P onto CG, meeting it at N, its length is b b We now have formed another two right angled triangles:

  • P G N PGN with sides P G = p g 2 , G N = f , P N = b PG=\frac{p-g}{2}, GN=f, PN=b
  • P C N PCN with sides P C = p c 2 , C N = h , P N = b PC=\frac{p-c}{2}, CN=h, PN=b
  • we also have G N + N C = G C GN+NC=GC , so f + h = g + c 2 f+h=\frac{g+c}{2}

Using similar techniques we find

f = ( f + h ) + ( f h ) 2 = g 2 + c g + p ( c g ) 2 ( c + g ) f=\frac{(f+h)+(f-h)}{2}=\frac{g^2+cg+p(c-g)}{2(c+g)} h = ( f + h ) ( f h ) 2 = c 2 + c g p ( c g ) 2 ( c + g ) h=\frac{(f+h)-(f-h)}{2}=\frac{c^2+cg-p(c-g)}{2(c+g)}

b = p c g ( p c g ) c + g b=\frac{\sqrt{pcg(p-c-g)}}{c+g}

We also find ( r p ) ( c g ) = ( g + c ) ( d e f + h ) = 2 ( g + c ) M N (r-p)(c-g)=(g+c)(d-e-f+h)=2(g+c)MN so that

M N = ( r p ) ( c g ) 2 ( c + g ) MN=\frac{(r-p)(c-g)}{2(c+g)}

Finally have an expression for RP: R P 2 = ( a + b ) 2 + M N 2 RP^2=(a+b)^2+MN^2

And the required length L can be found. Via

L = R P 2 ( r p 2 ) 2 = ( a + b ) 2 + M N 2 ( r p 2 ) 2 L=\sqrt{RP^2-(\frac{r-p}{2})^2}=\sqrt{(a+b)^2+MN^2-(\frac{r-p}{2})^2} we reach the general formula in terms of circle diameters: L = ( r c g ( r c g ) c + g + p c g ( p c g ) c + g ) 2 + ( ( r p ) ( c g ) 2 ( c + g ) ) 2 ( r p 2 ) 2 L=\sqrt{(\frac{\sqrt{rcg(r-c-g)}}{c+g}+\frac{\sqrt{pcg(p-c-g)}}{c+g})^2+(\frac{(r-p)(c-g)}{2(c+g)})^2-(\frac{r-p}{2})^2}

it can be rewritten to meet the appropriate leading term:

L = 2 c g / 6 c + g 3 r p 3 2 ( r + p ) ( c + g ) + 3 r p ( r c g ) ( p c g ) L=\frac{2\sqrt{cg/6}}{c+g}\sqrt{3rp-\frac{3}{2}(r+p)(c+g)+3\sqrt{rp(r-c-g)(p-c-g)}}

This is not yet the requested form so we have to solve (note that these are not the same a , b , c a,b,c as earlier) ( a b + c ) 2 = 3 r p 3 2 ( r + p ) ( c + g ) + 3 r p ( r c g ) ( p c g ) (a\sqrt{b}+\sqrt{c})^2=3rp-\frac{3}{2}(r+p)(c+g)+3\sqrt{rp(r-c-g)(p-c-g)} so that a 2 b + c = 3 r p 3 2 ( r + p ) ( c + g ) = 54100578693 a^2b+c=3rp-\frac{3}{2}(r+p)(c+g)=54100578693 and a 2 b c = 9 r p ( r c g ) ( p c g ) = 2 × 3 5 × 11 × 59 × 167 × 907 × 43963 × 314159 a^2bc=9rp(r-c-g)(p-c-g)=2×3^5×11×59×167×907×43963×314159 we find a = 9 , b = 11 × 907 × 43963 = 438618851 , c = 2 × 3 × 59 × 167 × 314159 = 18572451762 a=9, b=11×907×43963=438618851, c=2×3×59×167×314159=18572451762 a + b + c = 19011070622 a+b+c=\boxed{19011070622}

Matt Janko
Oct 6, 2020

Let r 1 r_1 , r 2 r_2 , r 3 r_3 , and r 4 r_4 denote the radii of the green, blue, purple, and red circles, respectively, and let the green and blue circles be centered at ( 0 , r 1 ) (0,r_1) and ( 0 , r 2 ) (0,-r_2) , respectively. The distance between the centers of the purple and green circles is r 3 r 1 r_3 - r_1 , while the distance between the centers of the purple and blue circles is r 3 r 2 r_3 - r_2 . This means the center of the purple circle is at the right intersection of the circles x 2 + ( y r 1 ) 2 = ( r 3 r 1 ) 2 and x 2 + ( y + r 2 ) 2 = ( r 3 r 2 ) 2 , x^2 + (y - r_1)^2 = (r_3 - r_1)^2 \quad \text{and} \quad x^2 + (y + r_2)^2 = (r_3 - r_2)^2, which is at ( x 1 , y 1 ) = ( ( r 3 r 1 ) 2 ( y 1 r 1 ) 2 , ( r 1 r 2 ) r 3 r 1 + r 2 ) . (x_1,y_1) = \left(\sqrt{(r_3 - r_1)^2 - (y_1 - r_1)^2} , \frac {(r_1 - r_2)r_3}{r_1 + r_2} \right). Similarly, the center of the red circle is at the left intersection of the circles x 2 + ( y r 1 ) 2 = ( r 4 r 1 ) 2 and x 2 + ( y + r 2 ) 2 = ( r 4 r 2 ) 2 , x^2 + (y - r_1)^2 = (r_4 - r_1)^2 \quad \text{and} \quad x^2 + (y + r_2)^2 = (r_4 - r_2)^2, which is at ( x 2 , y 2 ) = ( ( r 4 r 1 ) 2 ( y 2 r 1 ) 2 , ( r 1 r 2 ) r 4 r 1 + r 2 ) . (x_2,y_2) = \left(\sqrt{(r_4 - r_1)^2 - (y_2 - r_1)^2} , \frac {(r_1 - r_2)r_4}{r_1 + r_2} \right).

Now consider the right triangle in the figure. The hypotenuse is the segment from ( x 1 , y 1 ) (x_1,y_1) to ( x 2 , y 2 ) (x_2,y_2) , and one of the legs has length r 4 r 3 r_4 - r_3 . The other leg has the same length as the segment of the tangent line. By the Pythagorean theorem, this length is ( x 1 x 2 ) 2 + ( y 1 y 2 ) 2 ( r 4 r 3 ) 2 , \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2 - (r_4 - r_3)^2}, and with a little effort one can show that this simplifies to 2 105458935 50381 ( 9 438618851 + 18572451762 ) . \frac {2 \sqrt{105458935}}{50381} \left(9 \sqrt{438618851} + \sqrt{18572451762} \right). Therefore, the desired value is 9 + 438618851 + 18572451762 = 19011070622 9 + 438618851 + 18572451762 = \boxed{19011070622} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...